Finding a role? the United Kingdom, 1970 - 1990 - Harrison, Brian Howard 1937- (Clarendon Press, 2011)
Seven analytic chapters in this book pursue the massive changes wrought in Britain between 1970 and 1990. They look in detail at the changes in international relations, landscape and townscape, social framework, family and welfare structures, economic policies and realities and government which had occurred by 1990.
Includes bibliographical references and index
Keywords: Geschichte 1970-1990; Geschichte; Politik; Wirtschaft; Great Britain / Politics and government / 1964-1979; Great Britain / Politics and government / 1979-1997; Great Britain / Social conditions / 1945-; Great Britain / Economic conditions / 1964-1979; Great Britain / Economic conditions / 1979-1997; Großbritannien; Great Britain -- Economic conditions -- 1964-1979; Great Britain -- Economic conditions -- 1979-1997; Great Britain -- Politics and government -- 1964-1979; Great Britain -- Politics and government -- 1979-1997; Great Britain -- Social conditions -- 1945-; Handbuch